Placing Identity: Town, Land, and Authenticity in Nunavut, Canada - Searles, Edmund (Bucknell Digital Commons, 2010)
Recent demographic changes have made settlement patterns in the Canadian Arctic increasingly urban. Iqaluit, capital of Canada’s newest territory, Nunavut, is home to the largest concentration of Inuit and non-Inuit populations in the Canadian North. Despite these trends, Inuit cultural identity continues to rest heavily on the perception that to learn how to be authentically Inuit (or to be a better person), a person needs to spend time out on the land (and sea) hunting, fishing, trapping, and camping. Many Inuit also maintain a rather negative view of urban spaces in the Arctic, identifying them as places where Inuit values and practices have been eclipsed by Qallunaat (‘‘white people’’) ones. Some Inuit have even gone so far as to claim that a person is no longer able to be Inuit while living in towns like Iqaluit. This article examines those aspects of Canadian Inuit identity, culture, and tradition that disfavor the acceptance of an urban cultural identity. Based on ethnographic research conducted on Baffin Island in the mid 1990s and early 2000s, the many ways Iqaluit and outpost camp Inuit express the differences and similarities between living on the land and living in town are described. Then follows an examination of how the contrast of land and town is used in the rhetoric of Inuit politicians and leaders. Finally, a series of counterexamples are presented that favor the creation of an authentic urban Inuit identity in the Arctic, including recent attempts on the part of the Nunavut Territorial Government to make education and wage employment in the region more reliant on Inuit Qaujimajatuqangit, or Inuit traditional knowledge.1